Development of hybrid molecules of anti-tumour triazenes that target iron metabolism - Pires, André Filipe Neves Gonçalves Andrade (2021)
Tese de mestrado, Química Medicinal e Biofarmacêutica , 2021, Universidade de Lisboa, Faculdade de Farmácia.